Castleman disease: a rare case in a young woman - Paparella, Maria Teresa; Popolizio, Teresa; Grasso, Daniela; Serricchio, Ettore Angelo; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Castleman disease is a rare lymphoproliferative disorder characterized by benign enlargement of lymph nodes. It is divided into unicentric disease, which involves a single enlarged lymph node, and multicentric disease, which affects multiple lymph node stations. In this report, we describe a rare case of a 28-year-old female patient with an unicentric Castleman disease. Computed tomography and magnetic resonance imaging revealed a well-circumscribed large mass in the left neck, characterized by intense homogenous enhancement and suspected for a malignant disease. The patient underwent an excisional biopsy for definitive diagnosis of unicentric Castleman disease and ruled out malignant conditions.